Critical Review of the Disparity of Criminal Decisions in Narcotics Crime Cases: Tinjauan Kritis Terhadap Perbedaan Putusan Pidana dalam Kasus Tindak Pidana Narkoba - Wardani, Dona Febi (Annual Review of Legal Studies, 2024)
This research aims to identify disparities in criminal decisions regarding Decision Number 46/Pid.Sus/2022/PN.Tmg and Decision Number 48/Pid.Sus/2021, determine the factors that cause disparities in criminal decisions regarding these two decisions, and analyze the fulfillment of society's sense of justice. regarding the disparity between the two decisions. This research is the result of research using doctrinal or normative legal research methods. Data collection was carried out in two ways. One of them is literature study and the other is interviews as supporting material. The data sources for this research include secondary legal materials which consist of three legal materials, namely primary, secondary and tertiary legal materials. The research results show that the decisions studied by the author fulfill a sense of justice even though there are disparities in the decisions in the two decisions. Therefore, the suggestion regarding the results of this research is that the government is expected to update Article 112 Paragraph (1) and Article 127 Paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics so that there is no confusion in the articles and take quick steps to create a program regarding understanding the purpose of punishment for society, for law enforcers the law is expected to be able to understand it carefully and must look at every case of narcotics abuse from the perspective of public justice, for the Supreme Court and the Prosecutor's Office it is necessary to develop guidelines for handling cases or guidelines for sentencing in narcotics cases, for the panel of judges is expected to be able to explain and expressly explain the fairness of the decisions he has determined in his considerations.